The Economy of Education: Development, Challenges, and Prospects in Bosnia and Herzegovina - Pandza, Izet Karić; Hrebatć , Mehmet (Idarah (Jurnal Pendidikan dan Kependidikan), 2023)
The economy of education is understood as a financial transaction and a social investment with broad and sustainable effects (development of national civilization). This research aims to provide a brief overview of the development of the economy of education, highlight relevant literature, and discuss the problems and opportunities it offers. This research aims to identify critical factors in BiH's education economy that influence the country's educational development and economic growth. This research is qualitative and uses benchmarking. The research results explain the identification of several crucial factors in the economic pillars of education, i.e., government policy, the level of educators' welfare, education and training, information and communication technology (ICT), and research and development. Based on these findings, this research constructs measures and strategies to improve the development of the educational knowledge economy in Bosnia and Herzegovina. In addition to strategic policy factors, analyzing factors influencing the economic effectiveness of education in Bosnia and Herzegovina identified important elements such as fantastic location, cost-efficient education, internationally recognized education, and several interesting and contemporary study program options. The synergy between components in the education system results in educational excellence in quality and accessibility. A comprehensive and diverse education system prepares students for successful careers. An inclusive and multilingual environment encourages diversity and professional skills.